Photo-oligomerization by shifting the coordination site in a luminescent coordination polymer. Issue 17 (1st February 2021) - Song, Wei-Chao; Geng, Chen-Chen; Li, Sheng-Yang; Liang, Ling; Wang, Xiu-Guang; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : The photo-oligomerization of a diolefinic ligand by shifting the coordination site in a Zn II -based CP has been designed. Abstract : A layered coordination polymer (CP) with the fine-tuned alignment of four diolefinic ligands has been designed by shifting the coordination site of the ligand. The trimeric and tetrameric cyclobutane derivatives were reversely achieved by the photoinitiated [2+2] cycloaddition of the CP due to the favorable Schmidt's distance. More interestingly, a dynamic fluorescence shift was observed during the photo-oligomerization and heat-cycloreversion of the CP system.